Resilience and Support Networks for University Students with Disabilities - CedeÃƒÂ±o, MarÃƒÂa Leonila GarcÃƒÂa; Meza, Anicia Katherine Tarazona; MejÃƒÂa, Robert Gonzalo CedeÃƒÂ±o (International Research Journal of Management, IT & Social Sciences, 2018)
Resilience is a phenomenon that can be studied in catastrophic situations but also in everyday matters such as disability, this being an alternative way of working in the environment that requires the adaptation of the social networks that contain and support people with this condition. The research was conducted at the Technical University of ManabÃ applied to the population of students with disabilities. The paper presents an analysis of support networks and their relationship with student resilience. The results related to the application of the Saavedra-Villalta test are shown, which allowed to correlate the level of resilience of the sample studied with the support networks. An analysis linked to the interpretation of the Pearson correlation coefficient is presented. The result obtained is presented by applying semi-structured interviews to a sample of 48 disabled students.